2017
DOI: 10.18632/oncotarget.19544
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aldehyde dehydrogenase 1 enhances the cytotoxic effect of retinaldehyde on A549 cancer cells

Abstract: We hypothesized that aldehyde dehydrogenase1 (ALDH1) protects cancer cells from retinaldehyde-induced cytotoxicity, and that targeting this enzyme would enhance the therapeutic effect of retinaldehyde. ALDEFLUOR™ assays showed high ALDH activity in A549 and H522 cancer cells and low activity in H1666 and T47D cancer cells. Immunoblots showed that expression of ALDH1A1 and ALDH1A3 was high in A549 and H522 cells, but low in H1666 cells. HPLC confirmed that N, N-diethylaminobenzaldehyde (DEAB) inhibits ALDH-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…In cholangiocarcinoma, the reduction of ALDH activity in gemcitabine-resistant cells by metronidazole resulted in the enhancement of chemosensitivity (23). In lung cancer, inhibiting ALDH with DEAB and disulfiram suppressed the viability of cancer cells and sensitized the cancer cells to chemotherapy (10,11). Consistent with these data, in the present study, after comparing untreated cells and cells treated with DEAB, it was observed that an ALDH inhibitor (DEAB) reduced cell viability, cell quiescence and furthermore, enhanced gemcitabine-induced cytotoxicity in vitro.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In cholangiocarcinoma, the reduction of ALDH activity in gemcitabine-resistant cells by metronidazole resulted in the enhancement of chemosensitivity (23). In lung cancer, inhibiting ALDH with DEAB and disulfiram suppressed the viability of cancer cells and sensitized the cancer cells to chemotherapy (10,11). Consistent with these data, in the present study, after comparing untreated cells and cells treated with DEAB, it was observed that an ALDH inhibitor (DEAB) reduced cell viability, cell quiescence and furthermore, enhanced gemcitabine-induced cytotoxicity in vitro.…”
Section: Discussionsupporting
confidence: 90%
“…Aldehyde dehydrogenase (ALDH) is a family of enzymes involved in the metabolism of intracellular aldehydes to acids by an NAD(P) + dependent reaction (6). ALDH activity is regarded as a marker for both normal and malignant stem cells in the hematological system and in the solid organ system, including pancreas, lung, liver, breast, colon and ovary organs (6)(7)(8)(9)(10)(11)(12)(13). As an ALDH isoform, ALDH1 is a detoxifying enzyme responsible for oxidizing intracellular retinaldehyde to retinoic acid (6,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, our results also showed that TCS did not affect the expression of ALDH1A1, Apo E, ADRA2A, DPYD, COMT, TPMT, HTRA, or MTHFR, which all participate in drug resistance, but not by promoting drug metabolism or clearance. 31 40 These results confirmed the specificity of TCS function.…”
Section: Discussionsupporting
confidence: 72%
“…Acetaldehyde oxidation to acetate will produce NADH and its oxidation back to NAD + by the mitochondrial the respiratory chain will produce ROS (Zakhari, ). In addition, there is some controversy as to the antioxidant and prooxidant roles of retinoids and, specifically, retinaldehyde (Edge & Truscott, ; Keys & Zimmerman, ; Park et al, ). The recruitment of RALDH2 for acetaldehyde oxidation instead of retinoic acid production (Shabtai et al, ) would result in the accumulation of retinaldehyde with its suspected pro‐oxidant activity.…”
Section: The Etiology Of Fasdmentioning
confidence: 99%